Implementasi Program Adiwiyata Dalam Membentuk Karakter Peduli Lingkungan Di SMPN 2 Telukjambe Timur - Ihtiar Nurapriyadi; Fitri Silvia Sofyan; Tridays Repelita (Educatio, 2026)
The purpose of the research is to examine the implementation of the Adiwiyata Program in shaping the character of environmental care at SMPN 2 Telukjambe Timur, examine the role of the program in increasing environmental awareness, and examine the supporting and inhibiting factors for its implementation. This study applies a qualitative approach with a descriptive method. Data is collected through observation, interviews and documentation, while data analysis refers to the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study prove that the Adiwiyata Program is optimally implemented through environmentally friendly school policies, integration of environment-based education, participatory activities, and the provision of supporting facilities and infrastructure. This program contributes to shaping students' environmental awareness through habituating cleanliness behavior, waste management, greening activities, and active involvement in various environmental activities. The effectiveness of the program depends on the collaboration of all school stakeholders despite persistent challenges such as student indiscipline and lack of family support